Aplikasi Sistem Informasi Geografis (SIG) dan Penginderaan Jauh untuk Pemetaan Daerah Penangkapan Ikan Tuna Mata Besar di Selatan Jawa dan Bali - Kadek Bagus Padmaningrat; I Wayan Gede Astawa Karang; Abd. Rahman As-syakur (Journal of Marine and Aquatic Sciences, 2017)
Bigeye tuna is the dominant species of tuna caught in the territorial waters of the Indian Ocean and a productive tropical species which accounts for more than 10% of the total catch in the whole world. Distribution of bigeye tuna can be predicted through optimum temperature associated with the presence of bigeye tuna and distribution of chlorophyll-a is associated with the presence of small pelagic fish. The distribution of sea surface temperature and chlorophyll-a can be detected through remote sensing systems. The purpose of this study was to determine the relationship between sea surface temperature and chlorophyll-a by the number of bigeye tuna catches in the waters south of Java and Bali, and mapped the area catching bigeye tuna in the waters south of Java and Bali. The method used is a second order polynomial regression analysis to determine the effect of sea surface temperature and chlorophyll-a by the number of bigeye tuna catches as well as correlation analysis to determine the relationship of sea surface temperature and chlorophyll-a by the number of bigeye tuna catches. Sea surface temperature and chlorophyll-a is related to the number of bigeye tuna catches.  The results of the analysis showed a strong relationship between sea surface temperature and chlorophyll-a by the number of bigeye tuna catches. Bigeye tuna fishing grounds in the waters south of Java and Bali are in a position 12oS-15oS and 106°E-118°E.